A Classroom Interaction Analysis of Teacher and Students by Using FIACS - Paulus Sainyakit; Yan Imam Santoso (Universitas Muhammadiyah Kalimantan Timur, 2024)
Classroom interaction plays an important role in the teaching and learning process. It is because it involves the interaction between teacher, student and student-student in which they influence each other in the classroom interaction. It is also said that classroom interaction gives a chance to ask, to guess, to think even to the course material in order to make interaction between the teacher and students their selves in the classroom. This research is aimed to analyze the classroom interaction by using FIACS. This research is included as a quantitative content analysis design. This research involves a teacher and the 2nd semester students of STKIP Terang Bangsa. The observation is employed in this research as the method of collecting data. After that, the data would be calculated by using a formula. The results show that the Teacher Initiated category is the highest dominant in the classroom interaction. It has 3.422 or 95,50% out of 3.583 interactions in the classroom. Then, the Student-Initiated category has 161 or 4,50% of the total. Lastly, the Student-student initiated category has no interactions. Due to the limitations of the research, the researcher suggests that future research on this topic should involve more participants in interacting not only teacher to student but student to student, so the conclusion can be drawn more valid.